Kekuatan Persepsi: Ekplorasi Citra Negara, Kualitas, Nilai, dan Niat Membeli Kembali Merek Ponsel Cerdas Tiongkok - Firmansyah*, Yayan; Hardiyanto, Nugroho; Rafdinal, Wahyu; Juniarti, Cahaya (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
The role of a country's image in changing consumer views can encourage consumers to repurchase products from that country. This study focuses on the effect of a country's image on repurchase intentions with the additional influence of perceived value and perceived quality. This research method uses an explanatory method with a quantitative approach. The sampling technique used is purposive sampling technique with smart phone users and has purchased Chinese brand smart phones more than twice as a sample. The results obtained show that country image has a significant effect on repurchase intention, besides that other constructs such as perceived value and perceived quality also have a significant effect on repurchase intention. Keywords: Country Image; Perceived Quality; Perceived Value; Repurchase Intention; Smartphone